2005
DOI: 10.1007/bf03337720
|View full text |Cite
|
Sign up to set email alerts
|

The Caregiver Burden Inventory in evaluating the burden of caregivers of elderly demented patients: results from a multicenter study

Abstract: The CBI proved to be an effective multidimensional tool for evaluating the impact of burden on many aspects of caregivers' lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
97
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 31 publications
12
97
2
Order By: Relevance
“…The multidimensionality of caregiver burden -as we found -is not generally discussed (Bartolo, et al, 2010;Caserta, et al, 1996;Marvardi, et al, 2005;Savundranayagam, et al, 2010). But our findings did raise the question about the stability and reliability of these dimensions.…”
Section: A Caregiver Burden Scale (23 Items) Is Used On a Regular Bascontrasting
confidence: 64%
See 3 more Smart Citations
“…The multidimensionality of caregiver burden -as we found -is not generally discussed (Bartolo, et al, 2010;Caserta, et al, 1996;Marvardi, et al, 2005;Savundranayagam, et al, 2010). But our findings did raise the question about the stability and reliability of these dimensions.…”
Section: A Caregiver Burden Scale (23 Items) Is Used On a Regular Bascontrasting
confidence: 64%
“…For example, the Caregiver Burden Inventory mentions five dimensions, called "time burden", "physical burden", "personal development burden", "emotional burden", and "social burden" . These dimensions were not always in research found (Marvardi, et al, 2005), while other authors used a total score and accepted the dimensions as granted (Bartolo, et al, 2010). Other authors prefer -for practical or theoretical reasons -other dimensions (Savundranayagam, Montgomery, & Kosloski, 2010).…”
Section: A Caregiver Burden Scale (23 Items) Is Used On a Regular Basmentioning
confidence: 99%
See 2 more Smart Citations
“…This test quantifies burdens in several aspects of a caregiver's life, as well as the influence of patients' and caregivers' characteristics on its different dimensions. Previous assessments of the CBI have found it to be of high internal consistency (Marvardi et al, 2005). The scale was adapted but not validated for this study by translating the English version into German, and only two of five subscales appropriate to this study were used.…”
Section: Pre and Post Measurements Of Pwds And Caregiversmentioning
confidence: 99%